Metabolism of cryptolepine and 2-fluorocryptolepine by aldehyde oxidase - Stell, J. Godfrey P.; Wheelhouse, Richard T.; Wright, Colin W. (Journal of pharmacy and pharmacology, 2012)
Objectives To investigate the metabolism of cryptolepine and some cryptolepine analogues by aldehyde oxidase, and to assess the implications of the results on the potential of cryptolepine analogues as antimalarial agents. Methods The products resulting from the oxidation of cryptolepine and 2-fluorocryptolepine by a rabbit liver preparation of aldehyde oxidase were isolated and identified using chromatographic and spectroscopic techniques. The antiplasmodial activity of cryptolepine-11-one was assessed against Plasmodium falciparum using the parasite lactate dehydrogenase assay. Key findings Cryptolepine was oxidized by aldehyde oxidase give cryptolepine-11one. Although 2-fluorocryptolepine was found to have less affinity for the enzyme than cryptolepine, it was a better substrate for aldehyde oxidase than the parent compound. In contrast, quindoline, the 11-chloro-, 2,7-dibromo-and 2-methoxy analogues of cryptolepine were not readily oxidized. Cryptolepine-11-one was found to be inactive against P. falciparum in vitro raising the possibility that the effectiveness of cryptolepine as an antimalarial, may be compromised by metabolism to an inactivemetabolite by liver aldehyde oxidase. Conclusions Cryptolepine and 2-fluorocryptolepine are substrates for aldehyde oxidase. This may have implications for the design and development of cryptolepine analogues as antimalarial agents.